2021
DOI: 10.1002/pat.5427
|View full text |Cite
|
Sign up to set email alerts
|

Induced assembly of polystyrene composites for simultaneously improving flame retardant and electromagnetic shielding properties

Abstract: Polystyrene/silicon wrapped ammonium polyphosphate/reduced graphene oxide (PS/SiAPP/rGO) composites with satisfactory flame retardant and electromagnetic interference (EMI) shielding properties were prepared by the approaches of filtration induced assembly and hot‐pressing. The results indicated that the SiAPP and rGO exhibited good dispersivity in the PS matrix. The introduction of the SiAPP and rGO promoted the thermal and fire‐safe performances of PS composites. Moreover, the peak of heat release rate and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…17 Caiqin Gao synthesized silicon wrapped ammonium polyphosphate (SiAPP) by microencapsulating APP, the peak heat release rate (PHRR) and total heat release (THR) of the polystyrene (PS) containing 10 wt% SiAPP and 10 wt% reduced graphene oxide (rGO) decrease by 47.2% and 30.3%, respectively. 18 Chitosan (CS), a low-cost, non-toxic and biodegradable material, is selected as a char-forming agent. 19 Xiaoyu Gu et al reported that APP and CS can promote the formation of dense, uniform and continuous char residue in the PLA matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Caiqin Gao synthesized silicon wrapped ammonium polyphosphate (SiAPP) by microencapsulating APP, the peak heat release rate (PHRR) and total heat release (THR) of the polystyrene (PS) containing 10 wt% SiAPP and 10 wt% reduced graphene oxide (rGO) decrease by 47.2% and 30.3%, respectively. 18 Chitosan (CS), a low-cost, non-toxic and biodegradable material, is selected as a char-forming agent. 19 Xiaoyu Gu et al reported that APP and CS can promote the formation of dense, uniform and continuous char residue in the PLA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that microencapsulation technology can effectively improve the flame retardant (FR) efficiency of APP 17 . Caiqin Gao synthesized silicon wrapped ammonium polyphosphate (SiAPP) by microencapsulating APP, the peak heat release rate (PHRR) and total heat release (THR) of the polystyrene (PS) containing 10 wt% SiAPP and 10 wt% reduced graphene oxide (rGO) decrease by 47.2% and 30.3%, respectively 18 . Chitosan (CS), a low‐cost, non‐toxic and biodegradable material, is selected as a char‐forming agent 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of β-CD@SnPP on the burning behaviors of EP composites was evaluated through cone calorimeter, revealing some important parameters to comprehend the flame retardant and smoke suppression capabilities during burning progress [38]. Time to ignition (TTI) is a main indicator for determining flammability.…”
Section: The Combustion Performance Of Ep/β-cd@snpp Compositesmentioning
confidence: 99%
“…In recent years, there have been more and more studies on bifunctional and multifunctional additives with flame retardancy and other functions. Gao et al prepared PS/silicon-wrapped ammonium polyphosphate/multiwall carbon nanotube (PS/SiAPP/MWCNT) composites with a segregated structure via the methods of ball milling and hot pressing. The PS/SiAPP/MWCNT hybrid material was a satisfactory electromagnetic interference shielding material with excellent flame retardancy for electronic equipment .…”
Section: Introductionmentioning
confidence: 99%